Answer with Step-by-step explanation:
We are given that f(x)=
![x^2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/lj2p7ilwuzg3rb119glsof4tows22y4e2d.png)
![g(x)=√(x)+3](https://img.qammunity.org/2020/formulas/mathematics/high-school/xgxdqfv2hlv44gb300c9jon6ebd6ckf1gb.png)
a.We have to show that
![g(f(x+3))=\mid{x+3}\mid +3](https://img.qammunity.org/2020/formulas/mathematics/high-school/bipwjk4q8bff774e1um1osewjmxc8ct8ck.png)
![g(f(x+3))=√((x+3)^2)+3](https://img.qammunity.org/2020/formulas/mathematics/high-school/xaa4u2b82ry3wt6odzyhn1k0bpogz8dl8k.png)
When we remove square root then we take plus minus therefore we write in modulus.
Therefore,
![g(f(x+3))=\mid {x+3}\mid+3](https://img.qammunity.org/2020/formulas/mathematics/high-school/sj3ne200vdsg804aoheafn5za4qid1qk01.png)
Hence, proved.
b.We have to find that
![g(x)=\mid{x+3}\mid+3=\mid x\mid+6](https://img.qammunity.org/2020/formulas/mathematics/high-school/f8t5g08iod9jkgfb91fbzwitnk3tg20zw3.png)
Substitute x=-3
Then, we get
![g(x)=\mid{-3+3}\mid+3=3](https://img.qammunity.org/2020/formulas/mathematics/high-school/5s4e2ndp630xcu42ztnjox7txksmw4t99c.png)
![g(x)=\mid{-3}\mid+6=9](https://img.qammunity.org/2020/formulas/mathematics/high-school/oqjsguet62y461pszf7iky3arvmcub15vn.png)
![3\\eq 9](https://img.qammunity.org/2020/formulas/mathematics/high-school/qkb8ads29f23hsue0evrbh17gyykpjb2ph.png)
for
![x\geq 0](https://img.qammunity.org/2020/formulas/mathematics/college/gjkumktjuetfceaetyi4mh97u8esghiav9.png)
But,
for x<0
Hence,
for all x.